P17.02.A IPAX-1: phase 1/2 study of131I-iodo-phenylalanine (131IIPA) combined with external radiation therapy as treatment for patients with relapsed glioblastoma. (5th September 2022) - Pichler, J; Leibetseder, A; Höllmüller, I; Traub-Weidinger, T; Fitz, F; Geinitz, H; Feichtinger, J; Brown, T; Hayward, C
Abstract: Background: A novel therapeutic approach using molecularly targeted radiation is currently in development for patients with recurrent GBM. Many tumor types, including GBM, overexpress the L-type amino transporter 1 (LAT-1)4, which is able to internalize the small-molecule amino acid derivative, 4-L-[131I] iodo-phenylalanine (131I-IPA). In preclinical research, combining 131I-IPA with external radiation therapy (XRT) yielded additive cytotoxic effects. Tumoral accumulation of 131I-IPA was confirmed in a proof-of-principle study using single doses of 2-7 GBq 131I-IPA as a monotherapy or in combination with XRT in patients with recurrent GBM. The objective of the IPAX-1 study was to evaluate the safety, tolerability, dosing schedule, and preliminary efficacy of 131I-IPA in combination with second-line radiotherapy in patients with recurrent GBM. Methods: IPAX-1 is a multi-center, open-label, single-arm, dose-finding phase 1/2 study. Key inclusion criteria: 1. Confirmed histological diagnosis of GBM with evidence of first recurrence 2. History of GBM standard therapy 3. ≥ 6 months since end of first-line XRT 4. Pathologically increased amino acid tumor uptake shown by molecular imaging 5. Current indication for repeat radiation 6. Gross tumour volume of up to 4.8 cm diameter. Treatment: In phase 1 of the study patients received intravenous 131I-IPA at a dose level of 2 GBq administered in one of three different dosing regimens: single dose group with 2 GBq before radiation, 3 (f)-fractionated-parallel group: 3 x 0.67 GBq during XRT and 3 (f)-fractionated-sequential group: 0.67 GBq x 1 → XRT → 0.67 GBq x 2. XRT is delivered in 18 fractions of 2 Gy each. Results: 10 patients were randomized; one patient with Covid related death was withdrawn from analysis. Survival from start of TLX101 therapy showed mPFS2 of 4.33 M (95% -CI 4.18 - 4.48), PFS-6: 18 % and mOS2 of 15.97 M (95% -CI 2.9 - 29.1) at data lock 09/2021. Updated results will be presented at the meeting. Conclusion: There were no clinically relevant laboratory changes over time. Urinalysis, vital signs, and ECG did not show any clinically relevant changes from baseline. There were no notable differences in safety and tolerability between groups. Injections of single or fractionated doses of 131I-IPA containing a total activity of 2 GBq in combination with XRT in patients with recurrent GBM were safe and well tolerated. Survival data look promising; extension cohort will be treated in a phase II study in Linz; phase 1/2 study in first line setting is planned.